ANALYSIS OF LEGAL ASPECTS OF STORAGE OF MEDICAL PRODUCTS APPOINTED FOR MEDICAL AND SANITARY CONSEQUENCES OF EMERGENCIES MITIGATION - G. Ya. Ibragimova; R. V. Nasyrov; A. Kh. Gaisarov (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
The article analyzes principal legal aspects of medical products storage, appointed for medical and sanitary consequences of emergencies mitigation. We have revealed that nowadays there is a whole range of legal gaps and uncertainties in the regulation of medical products storage. We have also offered the ways for their solution